Weighing the Failure of the Anti-Violence Regional Regulation in Gorontalo: Regulatory Gaps or Weak Law Enforcement Apparatus? - Humaira Nur Bahtiar; Zamroni Abdussamad; Ahmad Ahmad (SEAN Institute, 2026)
This study analyzes the implementation of Gorontalo Provincial Regional Regulation Number 1 of 2016 concerning the Protection of Women and Children from Acts of Violence, focusing on identifying the dominant factors hindering its effectiveness. The background of this research is the fluctuating high rate of violence against women and children in Gorontalo Province over the past three years, indicating a gap between the existence of the regulation and field realities. This research employs an empirical legal method with a qualitative approach, collecting data through interviews, observation, and documentation studies, and analyzing it using the theory of legal effectiveness. The results indicate that while the Provincial Regulation is normatively adequate, regulatory gaps exist in the derivative regulations at the district/city level which are not yet harmonized. However, the dominant factor hindering implementation lies precisely in the weakness of the law enforcement apparatus and institutions, including the limited capacity of the Technical Implementation Unit for the Protection of Women and Children (UPTD PPA), the scarcity of professional experts, political and budgetary dynamics, weak cross-sectoral coordination, and data discrepancies between institutions. This study concludes that strengthening institutional capacity and the law enforcement apparatus is an absolute prerequisite for the effective implementation of Regional Regulation No. 1 of 2016 in Gorontalo Province.